2009
DOI: 10.2459/jcm.0b013e32831af028
|View full text |Cite
|
Sign up to set email alerts
|

Speckle-tracking-derived strain and strain-rate analysis: a technique for the evaluation of early alterations in right ventricle systolic function in patients with systemic sclerosis and normal pulmonary artery pressure

Abstract: Speckle-tracking-derived longitudinal strain rate is useful to detect early right ventricular function changes in patients with systemic sclerosis with normal pulmonary systolic artery pressure levels. This alteration may preclude pulmonary artery hypertension development and reflect an adaptive response to higher levels of pulmonary systolic artery pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 24 publications
2
22
0
2
Order By: Relevance
“…The introduction of the new STE method has enabled a more precise assessment of LV function [24] and enables regional and global assessment of the left ventricle. Previous studies have indicated that 2D STE is more sensitive than conventional echocardiography for detecting subclinical ventricular dysfunction in various clinical disorders [25,26]. Erdogan et al [27] reported that the GLS values decreased considerably in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of the new STE method has enabled a more precise assessment of LV function [24] and enables regional and global assessment of the left ventricle. Previous studies have indicated that 2D STE is more sensitive than conventional echocardiography for detecting subclinical ventricular dysfunction in various clinical disorders [25,26]. Erdogan et al [27] reported that the GLS values decreased considerably in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…RV LPSS was measured with speckle-tracking strain echocardiography. 11,12,14 Clinical and echocardiographic data were prospectively collected in the departmental Cardiology Information System (EPD-Vision, Leiden University Medical Center, Leiden, the Netherlands) and the echocardiography database and were retrospectively analyzed. All patients were followed-up for the occurrence of all-cause mortality.…”
Section: Patient Population and Data Collectionmentioning
confidence: 99%
“…Real-time three-dimensional echocardiography, for example, may provide quantitation of RV end-diastolic volume and other focused assessments of the RV. Likewise, two-dimensional speckletracking image analysis can assess myocardial deformation to inform about the extent of RV remodeling and strain; this may prove particularly useful in detecting subclinical PVD (which presumably predates PH) in the setting of subjects who are at risk of PH due to a coexistent condition, such as scleroderma (38).…”
Section: Novel Methods To Detect Pvd Before Pah Is Presentmentioning
confidence: 99%